Pelatihan Membuat Bahan Ajar Berbasis Android Menggunakan Bantuan I-Spring Untuk Guru-Guru Smp Negeri 1 Sukasari - Zakiah, Ismi; Ratna, Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The purpose of student service week (PPM) is to improve and provide knowledge related to the use of android in maximizing online learning. The method used in the implementation of this PPM uses descriptive qualitative methode. The steps taken in the implementation of this PPM are as follows: (1) socialization, (2) initial observation in the form of interviews, (3) implementation of training, (4) examining learning devices and simulation of i-spring usage and, (5) implementation of android-based learning with the recommended assistance of i-spring and, (6) bills in the form of questionnaire results that have been filled by respondents, (7) final evaluation. PPM results were found that making android-based teaching materials using the help of i-spring for teachers of SMP Negeri 1 Sukasari is very useful to improve the ability of teachers in designing an android-based learning. This is evidenced by the implementation of questionnaires that have been filled by respondents on average more than 60% increase. But some things that must be considered in the application of making android-based teaching materials is the availability of teachers in designing teaching material devices using i-spring as well as the availability of other support such as internet data in maximizing online learning